Acute correction of proximal tibial coronal plane deformity in small children using a small monolateral external fixator with or without cross-pinning. (June 2021) - Lim, Chaemoon; Shin, Chang Ho; Yoo, Won Joon; Cho, Tae-Joon
Abstract: Purpose: Surgical correction of proximal tibia deformity in small children can be challenging. We present the surgical technique and outcome of proximal tibia osteotomy fixed with small monolateral external fixator in this patient group. Methods: A total of 17 cases in eight patients younger than nine years of age were study subjects. A proximal tibia osteotomy was fixed with a small monolateral external fixator with or without cross-pinning. Outcome was evaluated by changes of radiographic parameters such as medial proximal tibia angle (MPTA), metaphyseal diaphyseal angle (MDA) and clinical findings of complications, time interval until weight bearing and fixator removal time. Results: MPTA improved from a preoperative mean of 73° (sd 4°; 66° to 78°) to an immediate postoperative mean of 90° (sd 3°; 85° to 96°) in varus tibiae, and from 104° (sd 1°; 103° to 105°) to 89° (sd 1°; 88° to 89°) in valgus tibiae. In all, 15 of the 17 cases (88.3 %) achieved postoperative MPTA within the normal range (85° to 90°). MDA improved from a preoperative mean of 19° (sd 5°; 11° to 24°) to an immediate postoperative mean of 0° (sd 4°; -6° to 7°) in varus tibiae, and from -25° (sd 2°; -22° to -24°) to 2° (SD 1°; 1° to 3°) in valgus tibiae. Full weight bearing was possible at mean 1.7 months (0.5 to 3.0). Mean follow-up period was 6.5 years (sd 5.4; 1.0 to 16.0). No complications developed during the follow-up. Conclusion: Proximal tibia osteotomy fixed with small monolateral external fixator provides accurate, safe and efficient correction in the management of coronal plane angular deformity in small children. Level of Evidence: Level IV